INDIVIDUAL METHODS AND MEANS OF SPEED-STRENGTH TRAINING FOR WRESTLERS - Shaxzod Xushvaqtov (European Science Publishing, 2024)
Speed-strength qualities hold significant importance in wrestling, as highlighted by many authors and researchers. Recent studies and observations indicate a marked increase in their relevance in recent years. According to numerous experts, the growing demands for the spectacularity of wrestling competitions necessitate a shift in the approach to previously employed training methods. The need to increase the tempo of matches requires the demonstration of both absolute and explosive strength. A wrestler must display a high level of preparedness from the very start of the competition.
Keywords: Sports wrestling, intermuscular coordination, muscle reactivity, speed-strength training, speed-strength qualities, neuromuscular system, explosive strength, circuit method.